Review of Aerial Manipulator and its Control - Xu Wei-hong; Cao Li-jia; Zhong Chun-lai (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
The aerial manipulator is a new type of aerial robot with active operation capability, which is composed of a rotary-wing drone and an actuator. Although aerial manipulation has greatly increased the scope of robot operations, the research on aerial manipulators also faces many difficulties, such as the selection of aerial platforms and actuators, system modeling and control, etc. This article attempts to collect the research team’s Achievements in the field of aerial robotic arms. The main results of the aerial manipulator system and corresponding dynamic modeling and control are reviewed, and its problems are summarized and prospected.